Self-sensing lightweight phosphogypsum aggregate and preparation method thereof
By adding conductive fibers to the phosphogypsum core and conductive flexible coating of self-perception concrete, a mesh conductive path structure is formed, which solves the problems of conductive path obstacles and insufficient perception accuracy, and achieves the versatility of lightweight, internal maintenance, and self-perception, and reduces costs and solid waste treatment problems.
Patent Information
- Application Number
- CN202411903552.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing self-perception concrete faces problems such as conductive path barriers, insufficient perception accuracy, high cost and difficulty in consuming solid waste.
By adding conductive fibers to the core and conductive flexible coating of phosphogypsum, a special mesh conductive path structure is formed, which enhances the conductivity and perception of concrete, and uses the hydration reaction of phosphogypsum with cement to provide strength, while using foaming agents and polyurethane elastomers to reduce density.
It achieves lightweight, internal curing, self-perception versatility, enabling more precise perception of cracks and other damage types, reducing costs, and improving the sustainability of concrete.
Smart Images

Figure CN119898979A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and in particular relates to a self-sensing internally-cured lightweight phosphogypsum aggregate and a preparation method thereof. Background Art
[0002] With the rapid development and popularization of computer technology, the development of information technology has provided a foundation for building intelligence. The construction field has gradually applied computer technology to building design, construction management, operation and maintenance. At the same time, through big data analysis and cloud computing technology, real-time monitoring and optimization management of building operation status can be achieved, which plays an important role in self-sensing concrete. Self-sensing concrete is used in various building structures, such as bridges, buildings, tunnels, etc., as well as important infrastructure projects. It can help engineers and architects better monitor the health of the structure, detect potential problems in time, and improve the safety and reliability of the structure. It relies on the development of sensor technology, Internet of Things technology, big data and cloud computing technology, as well as the increasing demand for the safety and sustainability of building structures. Using the built-in sensor network, these sensors can monitor the physical parameters of concrete structures such as stress, strain, temperature, humidity, etc. The sensor signals can be transmitted to the data acquisition system wirelessly or wired for real-time monitoring and analysis.
[0003] Despite its great potential, self-sensing concrete still faces some challenges. First, traditional coarse aggregates are usually non-conductive, which poses an obstacle to the conductive path in self-sensing concrete. To overcome this obstacle, researchers have tried to use conductive aggregates, such as iron ore, as aggregates. However, the electrical signals of these conductive aggregates are rough, which may affect the sensing accuracy because the conductivity they introduce may not be uniform or stable enough. Second, currently self-sensing concrete is mainly used to sense the cracking law of cracks, which is an important application in structural health monitoring. However, this sensing ability is relatively limited because it mainly focuses on the formation and expansion of cracks, and the sensing ability may be insufficient for other types of damage, such as corrosion or fatigue. Third, the current cost of self-sensing concrete is relatively high, mainly due to its special materials and manufacturing processes. In addition, self-sensing concrete is often difficult to consume solid waste during the production process, which limits its application in the field of sustainable building materials.
[0004] With the acceleration of the modernization process and the continuous development of industry, the amount of industrial solid waste has increased year by year. Due to poor management or lack of effective treatment facilities, industrial solid waste is often directly landfilled or incinerated, which not only wastes resources but also pollutes the environment. Phosphogypsum is a common industrial solid waste, which may contain harmful substances such as radioactive elements and heavy metals. If improperly handled, it may pollute the environment. The reasonable treatment of phosphogypsum requires advanced technology and equipment, is difficult to handle, and is generally used at a low value. Therefore, this patent utilizes the ability of phosphogypsum to react with cement to generate high-sulfur calcium sulfoaluminate hydrate, and dopes a certain amount of conductive fibers, admixtures, polymers, etc. to prepare lightweight aggregates with internal curing effects and self-sensing effects, solving the problems of phosphogypsum being difficult to use, poor accuracy of self-sensing aggregates, and high costs. Summary of the invention
[0005] The technical problem to be solved by the patent of the present invention is to provide a new functional self-sensing lightweight aggregate and its preparation method in view of the above shortcomings. The self-sensing lightweight aggregate of the present invention can not only provide basic strength for concrete, but also has multiple functional characteristics of light weight, internal curing, and self-sensing. It can sense the formation and expansion of cracks, and also has the performance of self-sensing for other types of damage.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] In one aspect of the present invention, a self-sensing lightweight phosphogypsum aggregate is provided, comprising a phosphogypsum core and a conductive flexible coating wrapped on the surface of the phosphogypsum core; the raw materials of the phosphogypsum core include phosphogypsum and 1% to 5% by weight of conductive fiber, and the raw materials of the conductive flexible coating include polyurethane elastomer, 1% to 10% by weight of conductive filler and 2% to 5% by weight of conductive fiber.
[0008] The present invention forms a special mesh conductive path structure - a conductive network - by adding conductive fibers in a specific proportion to the inner core of the self-sensing lightweight phosphogypsum aggregate and the conductive flexible coating, and matching the conductive filler with a specific content in the conductive flexible coating. This structure not only effectively connects the inner core and the conductive flexible coating, enhances the interface connection strength, and ensures the basic strength of the concrete, but also further enhances the conductive path of the concrete, improves the sensitivity of electrical signal transmission, and can more easily identify and sense the formation and expansion of concrete cracks. It can also sense different external force levels, deformation levels, dryness levels, and whether the external concrete is cracked, thereby achieving the self-sensing performance of the concrete for stress, strain, and fatigue damage under different loads.
[0009] On the basis of the above technical solution, the conductive fibers in the phosphogypsum core are of the same type and have the same function as the conductive fibers in the conductive flexible coating.
[0010] On the basis of the above technical solution, the conductive fiber is one or a combination of stainless steel fiber, conductive aramid fiber, semi-carbonized polyacrylonitrile fiber, and the specific resistance is 10 -2 ~10 -4 Ω·cm, fiber diameter 0.2~0.6mm, fiber length 2~5mm.
[0011] On the basis of the above technical solution, the particle size of the self-sensing lightweight aggregate is 10-20 mm, wherein the particle size of the inner core of the self-sensing lightweight aggregate is 8-18 mm, and the thickness of the conductive flexible coating of the self-sensing lightweight aggregate is 2-3 mm. The bulk density of the self-sensing lightweight aggregate is 800 kg / m 3 ~1200kg / m 3 .
[0012] Based on the above technical solution, the raw materials of the phosphogypsum core of the self-sensing lightweight aggregate include phosphogypsum, red mud, fly ash, cement, foaming agent A and conductive fiber; the raw materials of the conductive flexible coating include polyurethane elastomer, conductive filler, foaming agent B and conductive fiber.
[0013] On the basis of the above technical solution, the phosphogypsum is obtained by modifying phosphogypsum powder with quicklime and then drying it at 40°C to constant weight. The phosphogypsum, red mud and fly ash are sieved through a 0.15 mm square hole sieve.
[0014] On the basis of the above technical scheme, the raw materials of the phosphogypsum core include, by weight percentage: 50% to 55% of phosphogypsum, 5% to 10% of red mud, 5% to 10% of fly ash, 10% to 15% of cement, 0.2% to 2% of foaming agent A, 1% to 5% of conductive fiber, and 20% to 25% of water; the raw materials of the conductive flexible coating include, by weight percentage, 86% to 93% of polyurethane elastomer, 1% to 10% of conductive filler, 0.2% to 1% of foaming agent B, and 2% to 5% of conductive fiber.
[0015] As a new type of solvent-free, pollution-free green material, polyurethane elastomer has good elasticity, wear resistance, toughness and corrosion resistance. Compared with polyurea, epoxy resin and other elastomers, although polyurethane elastomer has slightly lower hardness, its elasticity and toughness are better. In addition, adding conductive fillers to polyurethane elastomer makes it have certain conductive properties, and adding conductive fibers makes it more conducive to the conduction of electrical signals.
[0016] On the basis of the above technical solution, the foaming agent A can be a calcium salt foaming agent, which can improve its physical properties and reduce density. The main components of the calcium salt foaming agent are calcium carbonate (CaCO3) and some active agents, such as fatty acid salts. In concrete and cement products, calcium salt foaming agents form tiny bubbles by releasing gas in the material, thereby reducing the density of the material and producing a closed-cell structure in the product; it can also reduce density, improve thermal insulation performance, improve water absorption performance, improve construction performance, and have certain environmental protection.
[0017] On the basis of the above technical solution, the foaming agent B can be dimethyl ether, which is a surfactant-type foaming agent. The dimethyl ether foaming agent can react with the polyurethane prepolymer to generate a large amount of gas and solidify quickly.
[0018] On the basis of the above technical solution, the polyurethane elastomer is formed by spraying the isocyanate component solution (component A) and the hydroxyl compound component solution (component B) through a portable spray gun.
[0019] On the basis of the above technical scheme, the polyurethane elastomer comprises an isocyanate component and a hydroxyl compound component in a weight ratio of 1:(2.5-4), wherein the isocyanate component comprises, by weight percentage, 65%-85% of isocyanate and 15%-35% of polymer diol; the hydroxyl compound component comprises, by weight percentage, 65%-75% of chain extender, 0%-5% of catalyst and 20%-30% of plasticizer.
[0020] On the basis of the above technical scheme, the isocyanate is one or more combinations of diphenylmethane diisocyanate (MDI), liquefied MDI, toluene diisocyanate (TDI), etc.; the polymer diol is one or more combinations of polyester diol, polycaprolactone diol, etc.; the chain extender is one or more combinations of ethylene glycol, 1,4-butanediol, benzidine, etc.; the catalyst is one or more combinations of triethylamine, triethanolamine, propylenediamine, etc.; the plasticizer is one or more combinations of dioctyl phthalate, tributyl triphosphate, epoxidized polypropylene, etc.
[0021] Preferably, the conductive filler is one or more combinations of carbon black, graphene, and micron-sized indium tin oxide.
[0022] The second aspect of the present invention provides a method for preparing a self-sensing lightweight phosphogypsum aggregate, comprising the steps of:
[0023] 1) Mix cement, red mud, phosphogypsum, fly ash, foaming agent A and conductive fiber according to the proportion;
[0024] 2) The mixed powder is put into the ball forming machine for water spray granulation, and then cured and dried to constant weight to form the phosphogypsum core;
[0025] 3) The isocyanate component of the raw material of the polyurethane elastomer is placed in a rubber cylinder of the spray gun of the spray machine, and the conductive filler, foaming agent B, conductive fiber and the hydroxyl compound component of the raw material of the polyurethane elastomer are placed in another rubber cylinder of the spray gun. Then the air compressor provides power for the spray gun to push the piston forward, and the components in the two rubber cylinders are pushed into the mixing tube for mixing, and then atomized and sprayed through the nozzle onto the phosphogypsum core, and the process ends when the particle size of the conductive flexible coating is reached; water immersion curing is performed to obtain a self-sensing lightweight phosphogypsum aggregate.
[0026] On the basis of the above technical solution, in step 2), the disc-type ball-forming machine is used, and the disc-type ball-forming machine performs water spray granulation, with a rotation speed of 30-45 r / min and an inclination angle of 45-60°. Aggregates are formed into balls after 3-4 minutes, and then the aggregates continue to roll in the ball-forming disk for 5-10 minutes to form a core. The prepared aggregate core is placed in a laboratory water tank for curing at a temperature of 20±2°C. After curing for 24 hours, it is dried at 40°C to constant weight.
[0027] A third aspect of the present invention provides a self-sensing concrete, the raw materials of which include any of the self-sensing lightweight phosphogypsum aggregates described above or the self-sensing lightweight phosphogypsum aggregates prepared by the above method.
[0028] Compared with the prior art, the present invention is beneficial in that:
[0029] (1) The functional self-sensing lightweight aggregate of the present invention has the characteristics of light weight, internal curing, and self-sensing, because different foaming agents are added to the core of the aggregate and the conductive flexible coating, so that its weight is reduced, but it still has a certain strength, achieving the effect of light weight. At the same time, the aggregate has the characteristics of internal curing and self-sensing, and can sense the external force level, deformation level, dryness level and whether the external concrete is cracked, thereby improving the volume stability. The use of this aggregate not only has the ability to self-sensing when cracking and damaging, but also, due to the high elasticity of the conductive flexible coating, the concrete can achieve self-sensing performance for stress, strain, and fatigue damage under compression (unidirectional, quasi-bidirectional and tridirectional, as well as impact, monotonic and cyclic loading), tension (unidirectional, splitting tension, monotonic and cyclic loading), and bending (unidirectional and impact, three-point bending and four-point bending, monotonic and cyclic loading).
[0030] (2) Conductive fibers added to lightweight aggregates can improve the tensile strength of concrete, inhibit crack development, and thus improve bearing capacity and ductility. Adding conductive fibers to aggregates can improve resistivity while bridging cracks inside, thereby improving the brittleness of concrete. The self-sensing lightweight aggregate obtained by the method of the present invention has excellent conductivity, heat resistance, and softness, and can conduct electrical signals, making it lightweight and self-sensing.
[0031] (3) In the inner core, phosphogypsum will react with the cement hydration components to generate high-sulfur hydrated calcium sulfoaluminate, namely calcium aluminate, which can provide a certain strength to the aggregate; a certain amount of water will be stored in the pores inside it, which is beneficial to provide moisture for the curing of the aggregate; the mesh fibers doped in the inner core overlap with each other, which is beneficial to the transmission of signals and plays a certain role in dispersing stress, reducing volume deformation, and thus improving the strength and volume stability of the aggregate; the fibers between the inner core and the conductive flexible coating can play an effective connecting role and enhance the interface connection strength.
[0032] (4) The self-sensing lightweight phosphogypsum aggregate of the present invention contains a special conductive network inside. Compared with general conductive aggregates, the sensitivity of electrical signal transmission is better. When the concrete prepared with the self-sensing lightweight phosphogypsum aggregate is subjected to external stimulation (load and environmental factors), the electrical signal inside it will show a certain regularity; the characteristic electrical signal generated by the deformation of the conductive flexible coating is easier to identify and sense than the electrical signal of general materials. When the concrete is subjected to load, the conductive flexible coating of the aggregate will undergo a large deformation. This deformation changes the contact range and contact area of the conductive filler and the conductive fiber in the conductive flexible coating, and the electrical signal presented to the outside will also change accordingly. For example, when subjected to continuous pressure (no cracks appear in the concrete), the electrical signal (FCR) exhibits a slow upward trend. When cracks appear in the concrete, the FCR rises suddenly and shows different degrees of rise with the increase in the number and width of the cracks until the concrete is destroyed. Therefore, the addition of the self-sensing lightweight phosphogypsum aggregate enables the concrete to have self-sensing ability.
[0033] (5) For concrete containing the conductive flexible coated phosphogypsum lightweight aggregate of the present invention, it is easier to detect structural changes of the concrete, and the concrete can also be detected and managed more intelligently. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the self-sensing lightweight phosphogypsum aggregate structure. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention provides a self-sensing lightweight phosphogypsum aggregate, comprising a phosphogypsum core and a conductive flexible coating wrapped on the surface of the phosphogypsum core; the raw materials of the phosphogypsum core include phosphogypsum and 1% to 5% by weight of conductive fiber, and the raw materials of the conductive flexible coating include polyurethane elastomer, 1% to 10% by weight of conductive filler and 2% to 5% by weight of conductive fiber.
[0037] In some examples of the present invention, the conductive fiber is one or a combination of stainless steel fiber, conductive aramid fiber, semi-carbonized polyacrylonitrile fiber, and the specific resistance is 10 -2 ~10 -4 Ω·cm, fiber diameter 0.2~0.6mm, fiber length 2~5mm.
[0038] In some examples of the present invention, the particle size of the self-sensing lightweight aggregate is 10-20 mm, wherein the particle size of the inner core of the self-sensing lightweight aggregate is 8-18 mm, and the thickness of the conductive flexible coating of the self-sensing lightweight aggregate is 2-3 mm.
[0039] In a specific example of the present invention, the raw materials of the phosphogypsum kernel include, by weight percentage: 50% to 55% of phosphogypsum, 5% to 10% of red mud, 5% to 15% of fly ash, 10% to 15% of cement, 0.2% to 2% of foaming agent A, 1% to 5% of conductive fiber, and 20% to 25% of added water; the raw materials of the conductive flexible coating include, by weight percentage, 86% to 93% of polyurethane elastomer, 1% to 10% of conductive filler, 0.2% to 1% of foaming agent B, and 2% to 5% of conductive fiber.
[0040] In some examples of the present invention, the polyurethane elastomer is formed by spraying an isocyanate component solution (component A) and a hydroxyl compound component solution (component B) through a portable spray gun, and the polyurethane elastomer includes an isocyanate component and a hydroxyl compound component in a weight ratio of 1: (2.5 to 4), and the isocyanate component includes, by weight percentage, 65% to 85% of isocyanate and 15% to 35% of polymer diol; the hydroxyl compound component includes, by weight percentage, 65% to 75% of chain extender, 0% to 5% of catalyst, and 20% to 30% of plasticizer. The isocyanate is one or more combinations of diphenylmethane diisocyanate (MDI), liquefied MDI, toluene diisocyanate (TDI), etc.; the polymer diol is one or more combinations of polyester diol, polycaprolactone diol, etc.; the chain extender is one or more combinations of ethylene glycol, 1,4-butanediol, benzidine, etc.; the catalyst is one or more combinations of triethylamine, triethanolamine, propylenediamine, etc.; the plasticizer is one or more combinations of dioctyl phthalate, tributyl phosphate, epoxidized polypropylene, etc.
[0041] In some examples of the present invention, the conductive filler is one or more combinations of carbon black, graphene, micron-sized indium tin oxide, etc.
[0042] In some examples of the present invention, the phosphogypsum is obtained by modifying phosphogypsum powder with quicklime and then drying it at 40°C to constant weight.
[0043] The present invention also provides a method for preparing a self-sensing lightweight phosphogypsum aggregate, comprising the steps of:
[0044] S1. Mix cement, red mud, phosphogypsum, fly ash, foaming agent A and conductive fiber according to the proportion.
[0045] S2. The mixed powder is put into a ball forming machine and a disc ball forming machine is used for water spray granulation. The rotation speed is 30-45r / min and the inclination angle is 45-60°. Aggregates are obtained after 3-4 minutes. Then the aggregates continue to roll in the ball forming disk for 5-10 minutes to form the core.
[0046] S3. Place the prepared aggregate core in a laboratory water tank for curing at a temperature of 20±2°C. After curing for 24 hours, dry it at 40°C to constant weight.
[0047] S4. Place the dried aggregate core on a disc-type ball forming machine, then place the polyurethane elastomer A component in one rubber barrel of the spray gun according to the ratio, and place the polyurethane elastomer B component, conductive filler, foaming agent B, and conductive fiber in another rubber barrel of the spray gun. Then, the air compressor provides power for the spray gun to push the piston forward, push the components in the two rubber barrels into the mixing tube for mixing, and atomize through the atomization switch, and then spray out through the nozzle onto the aggregate core, and end when the particle size of the conductive flexible coating is reached.
[0048] S5. The obtained self-sensing lightweight phosphogypsum aggregate is subjected to water immersion curing as described above.
[0049] Unless otherwise specified, the self-sensing lightweight phosphogypsum aggregate in the following embodiments is prepared by the above method; in addition, in order to further illustrate and verify the technical solution of the invention, in the following embodiments, the cement type is ordinary Portland cement with a strength grade of 42.5, and the fly ash is first-class fly ash; the phosphogypsum is obtained by fully mixing phosphogypsum powder, quicklime and water, standing and aging for 24 hours, and then drying at 40°C to constant weight, wherein the phosphogypsum powder: quicklime: water = 100:50:1 (mass ratio); the phosphogypsum, red mud and fly ash are passed through a 0.15 mm square hole sieve; the foaming agent A is a calcium salt foaming agent, and the foaming agent B uses dimethyl ether as a foaming agent; the conductive filler uses carbon black; the isocyanate component includes 75% of isocyanate and 25% of a polymer diol, the isocyanate uses diphenylmethane diisocyanate (MDI), and the polymer diol uses polyester diol; the hydroxy compound component includes 70% of a chain extender, 5% of a catalyst, and 25% of a plasticizer, and the chain extender uses ethylene glycol; the catalyst uses triethylamine; the plasticizer uses dioctyl phthalate; the particle size of the self-sensing lightweight aggregate is made into 15mm, wherein the particle size of the inner core of the self-sensing lightweight aggregate is 13mm, and the thickness of the conductive flexible coating of the self-sensing lightweight aggregate is 2mm. The optional ranges of the size, foaming agent, conductive filler, and polyurethane elastomer of the self-sensing lightweight aggregate have been listed in the specification, and the self-sensing lightweight phosphogypsum aggregate obtained within the scope of the present invention can solve the technical problem of the present invention, so the data in the embodiment will not be exhaustive.
[0050] Example 1
[0051] A self-sensing lightweight phosphogypsum aggregate, wherein the raw materials of the phosphogypsum core include, by weight percentage: phosphogypsum is 52%, red mud is 8%, fly ash is 5%, cement is 12%, foaming agent A is 1%, conductive fiber is 2%, and water is 20%; the raw materials of the conductive flexible coating include, by weight percentage, 90% polyurethane elastomer, 5% conductive filler, 1% foaming agent B, and 4% conductive fiber; the polyurethane elastomer includes an isocyanate component and a hydroxyl compound component in a weight ratio of 1:3. The conductive fiber is a conductive aramid fiber with a specific resistivity of 10 -2 Ω·cm, fiber diameter 0.3mm, fiber length 3mm.
[0052] Example 2
[0053] A self-sensing lightweight phosphogypsum aggregate, wherein the raw materials of the phosphogypsum core include, by weight percentage: 50% phosphogypsum, 5% red mud, 7.5% fly ash, 13% cement, 1.5% foaming agent A, 3% conductive fiber, and 20% water; the raw materials of the conductive flexible coating include, by weight percentage, 86% polyurethane elastomer, 10% conductive filler, 0.2% foaming agent B, and 3.8% conductive fiber; the polyurethane elastomer includes an isocyanate component and a hydroxyl compound component in a weight ratio of 1:4. The conductive fiber is a semi-carbonized polyacrylonitrile fiber with a specific resistivity of 10 -2 Ω·cm, fiber diameter 0.2mm, fiber length 4mm.
[0054] Example 3
[0055] A self-sensing lightweight phosphogypsum aggregate, wherein the raw materials of the phosphogypsum core include, by weight percentage: phosphogypsum is 55%, red mud is 5%, fly ash is 5%, cement is 10%, foaming agent A is 0.2%, conductive fiber is 1%, and water is 23.8%; the raw materials of the conductive flexible coating include, by weight percentage, 92% polyurethane elastomer, 3% conductive filler, 0.5% foaming agent B, and 4.5% conductive fiber; the polyurethane elastomer includes an isocyanate component and a hydroxyl compound component in a weight ratio of 1:2.5. The conductive fiber is a stainless steel fiber with a specific resistivity of 10 -4 Ω·cm, fiber diameter 0.6mm, fiber length 5mm.
[0056] Comparative Example 1
[0057] A self-sensing lightweight phosphogypsum aggregate is basically the same as Example 1, with an equal amount of conductive filler replacing the conductive fibers in the inner core.
[0058] Comparative Example 2
[0059] A self-sensing lightweight phosphogypsum aggregate is substantially the same as Example 1, with an equal amount of conductive filler replacing the conductive fibers of the inner core and the conductive flexible coating.
[0060] Comparative Example 3
[0061] A self-sensing lightweight phosphogypsum aggregate is basically the same as Example 1, with an equal amount of conductive fibers replacing the conductive filler of the conductive flexible coating.
[0062] Comparative Example 4
[0063] A self-sensing lightweight phosphogypsum aggregate is basically the same as Example 1, and all the conductive fibers in the conductive flexible coating are added into the inner core.
[0064] Comparative Example 5
[0065] Commercially available lightweight core-shell phosphogypsum aggregate (no self-sensing performance), with a bulk density of 871kg / m 3 .
[0066] Test example
[0067] For the density and cylinder pressure strength test of the self-perceived lightweight phosphogypsum aggregate of Examples 1-3 and Comparative Examples 1-5, the density test refers to the test method for bulk density in "Light Aggregate and Its Test Method Part 2: Test Method for Light Aggregate" (GB 17431.2-2010-T); the cylinder pressure strength test refers to the test method for measuring light coarse aggregate particles by the pressure cylinder method in "Light Aggregate and Its Test Method Part 2: Test Method for Light Aggregate" (GB17431.2-2010-T). The results are shown in Table 1:
[0068] Table 1 Density and cylinder pressure strength test of self-perceived lightweight phosphogypsum aggregate
[0069]
[0070] The self-sensing lightweight phosphogypsum aggregate of the present invention has a density grade of 800-grade lightweight aggregate and has a higher cylinder pressure strength than lightweight aggregates of the same grade.
[0071] The self-sensing lightweight phosphogypsum aggregate of Examples 1-3 and Comparative Examples 1-4 was used to prepare self-sensing concrete. The raw materials of the concrete included: cement 450 kg / m 3 , fly ash 150kg / m 3 , silica fume 150kg / m 3 , self-sensing lightweight phosphogypsum aggregate 650kg / m 3 , fine aggregate 300kg / m 3 , conductive filler 40kg / m 3 , water reducing agent 30kg / m 3, water 289kg / m 3 The method for preparing the self-sensing lightweight phosphogypsum aggregate concrete comprises the following steps:
[0072] (1) Add fine aggregate, cement, silica fume and fly ash into a concrete mixer and premix for 2 minutes;
[0073] (2) Pour in self-sensing lightweight phosphogypsum aggregate and stir for 2 minutes;
[0074] (3) Pour water and water reducing agent and stir for 3 minutes;
[0075] (4) After the mixture in the stirring pot reaches a viscous flow state, evenly add the conductive filler and continue stirring for 2 minutes;
[0076] (5) After fresh concrete leaves the mixing pot, it is molded, vibrated, and shaped. The surface is covered with a waterproof film and the standard curing conditions specified in GB / T 50081 are adopted. After one day, the molds are removed and standard curing is carried out.
[0077] The specimens were subjected to four-point bending tests and resistance measurement experiments, and the collected data were processed and analyzed.
[0078]
[0079] Where R t is the specimen resistance measured at time t0, and R0 is the initial resistance of the concrete beam corresponding to time t0 before loading.
[0080]
[0081] in, COD is the crack opening displacement change value (mm), FCR is the corresponding resistance change rate increment (%).
[0082] The test results are shown in Table 2:
[0083] Table 2 Self-sensing performance test of lightweight phosphogypsum aggregate concrete
[0084]
[0085] Compared with the comparative example, the self-sensing lightweight phosphogypsum aggregate concrete prepared by the present invention has sensitive electrical signals and can more easily identify and perceive the formation and expansion of concrete cracks. This is mainly due to the composite use of the conductive filler and conductive fiber in Example 1 to improve the conductive network inside the concrete. Since the conductive filler is sensitive to microstructural changes, and the conductive fiber has resistance and conduction effects on macroscopic deformation, they can synergistically enhance the sensitivity of concrete to stress and strain perception. When the concrete is subjected to a small external force or the internal structure begins to change, obvious electrical signal changes can be generated. Compared with comparative examples 1-4, the damage inside the concrete can be discovered earlier, and it is easier to identify the generation and development of concrete cracks than the comparative examples, and the perception performance of cracks is more excellent.
[0086] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A self-sensing lightweight phosphogypsum aggregate, characterized in that: It comprises a phosphogypsum core and a conductive flexible coating wrapped on the surface of the phosphogypsum core; the raw materials of the phosphogypsum core comprise phosphogypsum and 1% to 5% by weight of conductive fiber; the raw materials of the conductive flexible coating comprise polyurethane elastomer, 1% to 10% by weight of conductive filler and 2% to 5% by weight of conductive fiber.
2. A self-sensing lightweight phosphogypsum aggregate according to claim 1, characterized in that: The conductive fiber is one or a combination of stainless steel fiber, conductive aramid fiber, semi-carbonized polyacrylonitrile fiber, and has a specific resistance of 10 -2 ~10 -4 Ω·cm, fiber diameter 0.2~0.6mm, fiber length 2~5mm.
3. A self-sensing lightweight phosphogypsum aggregate according to claim 1, characterized in that: The particle size of the self-sensing lightweight aggregate is 10-20 mm, wherein the particle size of the inner core of the self-sensing lightweight aggregate is 8-18 mm, and the thickness of the conductive flexible coating of the self-sensing lightweight aggregate is 2-3 mm.
4. The self-sensing lightweight phosphogypsum aggregate according to claim 1, characterized in that: The raw materials of the phosphogypsum core include, by weight percentage, 50% to 55% of phosphogypsum, 5% to 10% of red mud, 5% to 10% of fly ash, 10% to 15% of cement, 0.2% to 2% of foaming agent A, 1% to 5% of conductive fiber, and 20% to 25% of water; the raw materials of the conductive flexible coating include, by mass percentage, 86% to 93% of polyurethane elastomer, 1% to 10% of conductive filler, 0.2% to 1% of foaming agent B, and 2% to 5% of conductive fiber.
5. The self-sensing lightweight phosphogypsum aggregate according to claim 1, characterized in that: The polyurethane elastomer comprises an isocyanate component and a hydroxyl compound component in a weight ratio of 1:(2.5-4), wherein the isocyanate component comprises, by weight percentage, 65%-85% of isocyanate and 15%-35% of polymer diol; the hydroxyl compound component comprises, by weight percentage, 65%-75% of chain extender, 0%-5% of catalyst and 20%-30% of plasticizer.
6. A self-sensing lightweight phosphogypsum aggregate according to claim 5, characterized in that: The isocyanate is one or more combinations of diphenylmethane diisocyanate (MDI), liquefied MDI, and toluene diisocyanate (TDI); the polymer diol is one or more combinations of polyester diol and polycaprolactone diol; the chain extender is one or more combinations of ethylene glycol, 1,4-butanediol, and benzidine; the catalyst is one or more combinations of triethylamine, triethanolamine, and propylenediamine; the plasticizer is one or more combinations of dioctyl phthalate, tributyl triphosphate, and epoxidized polypropylene ester.
7. The self-sensing lightweight phosphogypsum aggregate according to claim 1, characterized in that: The conductive filler is one or more combinations of carbon black, graphene, micron-sized indium tin oxide, etc.
8. The self-sensing lightweight phosphogypsum aggregate according to claim 1, characterized in that: The phosphogypsum is obtained by modifying phosphogypsum powder with quicklime and then drying it to constant weight. The phosphogypsum, red mud and fly ash are sieved through a 0.15 mm square hole sieve.
9. A method for preparing a self-sensing lightweight phosphogypsum aggregate, characterized in that: Includes steps: 1) Mix cement, red mud, phosphogypsum, fly ash, foaming agent A and conductive fiber according to the proportion; 2) The mixed powder is put into the ball forming machine for water spray granulation, and then cured and dried to constant weight to form the phosphogypsum core; 3) The isocyanate component of the raw material of the polyurethane elastomer is placed in a rubber cylinder of the spray gun of the spray machine, and the conductive filler, foaming agent B, conductive fiber and the hydroxyl compound component of the raw material of the polyurethane elastomer are placed in another rubber cylinder of the spray gun. Then the air compressor provides power for the spray gun to push the piston forward, and the components in the two rubber cylinders are pushed into the mixing tube for mixing, and then atomized and sprayed through the nozzle onto the phosphogypsum core, and the process ends when the particle size of the conductive flexible coating is reached; water immersion curing is performed to obtain a self-sensing lightweight phosphogypsum aggregate.
10. A self-sensing concrete, characterized in that: The raw materials include a self-sensing lightweight phosphogypsum aggregate as described in any one of claims 1 to 8 or a self-sensing lightweight phosphogypsum aggregate prepared by the method described in claim 9.
Citation Information
Patent Citations
Phosphogypsum micro-expansion lightweight aggregate ultra-high performance concrete and preparation method thereof
CN118307270A
AI multi camera apparatus
KR1020210047523A
Encapsulated lightweight polymer aggregates
US20160332911A1
Self-sensing high performance fiber reinforced geopolymer composites
US20190031563A1
Encapsulated systems for the development of self- healing building materials
US20240150241A1